Educational Philosophy of John Dewey & Its Relevance to Evolve a National System of Education in India: Examining the Relevance of John Dewey's Educational Philosophy in the Indian Context (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The deficiency and irrelevance of our existing educational system with the life of people has purchased about a time of disillusionment in the adolescent. The youngsters are taught to store into memory the symbols, concepts, ideas, theories, which have been created and sorted out by society and thus give just a fragmentary perspective on life which brings about a greater amount of contention and confusion in their minds. In this examination, an endeavor was made to ponder the Relevance of Educational Thoughts of John Dewey to the Present Educational Context –In the present investigation, arbitrary testing method was embraced to choose an example of 150 Middle School Teachers and independent apparatus was utilized to gather information. The outcome uncovered that there is a noteworthy contrast among male and female center teachers with respect to discernment on relevance of educational thoughts of John Dewey to the present educational setting and its measurement – curriculum. John Dewey's educational philosophies are immediate result of their lives and they have given a pragmatic shape to their educational philosophy. They believe that present system of training is not competent to create scientific intelligent reasoning and light the flame of enquiry inside students. The same thing is for Indian Education System. Man becomes just a gear-tooth in the wheel of the social system and can't set out step out, because of dread and in capabilities. This blocks the intelligence of the person. The fundamental purpose of training is to stir the intelligence and scientific reasoning.